Neurodevelopmental and genetic findings in neonates with intracranial arteriovenous shunts: A case series - Campi, Francesca; De Rose, Domenico Umberto; Pugnaloni, Flaminia; Ronci, Sara; Calì, Monica; Pro, Stefano; Longo, Daniela; Lucignani, Giulia; Raho, Laura; Pisaneschi, Elisa; Digilio, Maria Cristina; Savarese, Immacolata; et al. (Frontiers in Pediatrics, 2023)
Background: Despite the latest advances in prenatal diagnosis and postnatal embolization procedures, intracranial arteriovenous shunts (AVSs) are still associated with high mortality and morbidity rates. Our aim was to evaluate the presentation and clinical course, the neurodevelopmental outcome, and the genetic findings of neonates with AVSs. Methods: In this retrospective observational study, medical records of neonates with cerebral AVSs admitted to our hospital from January 2020 to July 2022 were revised. In particular, we evaluated neuroimaging characteristics, endovascular treatment, neurophysiological features, neurodevelopmental outcomes, and genetic findings. Results: We described the characteristics of 11 patients with AVSs. Ten infants (90.9%) required embolization during the first three months of life. In 5/9 infants, pathological electroencephalography findings were observed; of them, two patients presented seizures. Eight patients performed Median Nerve Somatosensory Evoked Potentials (MN-SEPs): of them, six had an impaired response. We found normal responses at Visual Evoked Potentials and Brainstem Auditory Evoked Potentials. Eight patients survived (72.7%) and were enrolled in our multidisciplinary follow-up program. Of them, 7/8 completed the Bayley-III Scales at 6 months of corrected age: none of them had cognitive and language delays; conversely, a patient had a moderate delay on the Motor scale. The remaining survivor patient developed cerebral palsy and could not undergo Bayley-III evaluation because of the severe psychomotor delay. From the genetic point of view, we found a novel pathogenic variant in the NOTCH3 gene and three additional genomic defects of uncertain pathogenicity. Conclusion: We propose SEPs as an ancillary test to discern the most vulnerable infants at the bedside, particularly to identify possible future motor impairment in follow-up. The early identification of a cognitive or motor delay is critical to intervene with personalized rehabilitation treatment and minimize future impairment promptly. Furthermore, the correct interpretation of identified genetic variants could provide useful information, but further studies are needed to investigate the role of these variants in the pathogenesis of AVSs.